Relationship Between the Youth’s Perspectives on Suicide and Their Suicide-Related Experiences - Quintos, Mark Anthony (Social Sciences and Development Review, 2024)
This study sought to determine if there is a relationship between the suicide experiences of the youth (no prior suicide experience, experience of suicide ideation but not attempts, and experience of suicide attempts) and their perspectives on suicide. Undergraduate university students (n=308) were engaged as participants in the study. Data were obtained through a survey questionnaire and were analyzed through correlational tests. Findings showed a very salient divide in the perspectives about suicide between those with no prior suicide experience and those with experience of suicide attempts. The former tend to have very conservative views on suicide to the point that they prefer not to talk about the topic and downplay the prevalence of the phenomenon but nonetheless believe that it is a human duty to stop someone from committing suicide. The latter tend to have very liberal views that lean towards the acceptance of suicide and assisted suicide. These two groups and their diverging views present two possibilities that Philippine society may take. On one hand, suicide may be downplayed as an issue but may nonetheless have the people with the right conviction necessary for suicide prevention. On the other hand, suicide and assisted suicide may be more accepted in Philippine society such that socio-cultural, legal, and medical impediments to the act may be relaxed. The direction of suicide-related responses, including legislation and regulation/prevention, that Philippine society will eventually take may be dependent on how prevalent suicide attempts will be in the succeeding years.